Søren Johansen and Katarina Juselius: A bibliometric analysis of citations through multivariate bass models - Fragiskos Archontakis; Rocco Mosconi (Econometrics, 2021)
We showcase the impact of Katarina Juselius and Søren Johansen's contribution to econometrics using bibliometric data on citations from 1989 to 2017, extracted from the Web of Science (WoS) database. Our purpose is to analyze the impact of KJ and SJ's ideas on applied and methodological research in econometrics. To this aim, starting from WoS data, we derived two composite indices whose purpose is to disentangle the authors' impact on applied research from their impact on methodological research. As of 2017, the number of applied citing papers per quarter had not yet reached the peak; conversely, the peak in the methodological literature seem to have been reached around 2000, although the shape of the trajectory is very flat after the peak. We analyzed the data using a multivariate dynamic version of the well known Bass model. Our estimates suggest that the methodological literature is mainly driven by "innovators", whereas "imitators" are relatively more important in the applied literature: this might explain the different location of the peaks. We also find that, in the literature referring to KJ and SJ, the "cross-fertilization" between methodological and applied research is statistically significant and bi-directional.
Keywords: 330; bass diffusion model; bibliometrics; cointegration